Theater and Dialogue to Increase Youth's Intentions to Advocate for LGBTQQ People. (March 2016) - Wernick, Laura J.; Kulick, Alex; Dessel, Adrienne B.; Graham, Louis F.
Objective: This study evaluates the effectiveness of an intervention using theater and dialogue to raise awareness about homophobia and transphobia and increase intentions to participate in macro-level change efforts around lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQQ) issues. Methods: Using a pretest–posttest design, this study examines changes in advocacy intentions around LGBTQQ issues among middle school and high school students who participated in the intervention ( n = 515). Results: Students reported a significant increase in intentions to advocate. Existing intervention behaviors and increased recognition of homophobia/transphobia as problems were associated with greater increases in intention to advocate. Respondents with higher existing intervention behaviors, as well as White students and cisgender women, reported higher advocacy intentions compared to students of color and cisgender men. Further, we found indication of greater awareness of homophobia/transphobia as a problem in school. Conclusions: Youth-led theater and dialogue-based interventions may be a promising strategy for addressing heterosexism and genderism in schools.